Thermodynamic Analysis of Refrigeration Systems Using Eco-Friendly Refrigerants - Rahman, Siti Nur Aisyah; Smith, Michael Jonathan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The global transition toward environmentally sustainable refrigeration systems has intensified research on eco-friendly refrigerants with low global warming potential and zero ozone depletion potential. Conventional refrigerants such as R22 and R134a are increasingly restricted due to their adverse environmental impacts. This study presents a systematic thermodynamic analysis of refrigeration systems operating with eco-friendly refrigerants, based on an extensive synthesis of recent peer-reviewed literature. The research evaluates system performance using first and second law analyses, focusing on key indicators such as coefficient of performance, exergy efficiency, entropy generation, and environmental impact metrics. The methodological approach integrates comparative analysis across single-stage, cascade, and multi-evaporator refrigeration configurations employing hydrofluoroolefins, hydrocarbons, carbon dioxide blends, and emerging nano-refrigerants. The results indicate that refrigerants such as R290, R1234yf, R1234ze, and R744-based mixtures consistently demonstrate superior energy and exergy performance compared to conventional fluids. Cascade and multi-stage systems further enhance performance under ultra-low temperature applications. The study confirms that eco-friendly refrigerants can achieve both thermodynamic efficiency and environmental sustainability. These findings provide a robust scientific basis for refrigerant selection and system design in future refrigeration and air-conditioning applications.